"Top-down bottom-up" estimation of per capita cost of new-born care interventions in four regions of Ghana: Beyond implementation to scalability and sustainability - Robert Kaba Alhassan; Edward Nketiah-Amponsah; Nana A. Y. Twum-Danso; John Bawa; Williams Kwarah; Sebnem Ucer; Abdul Fatawu Ibn Abass (Health Economics Review, 2021)
Background: Limited financial, human and material health resources coupled with increasing demand for new-born care services require efficiency in health systems to maximize the available sources for improved health outcomes. Making Every Baby Count Initiative (MEBCI) implemented by local and international partners in 2013 in Ghana aimed at attaining neonatal mortality of 21 per 1000 livebirths by 2018 in four administrative regions in Ghana. MEBCI interventions benefited 4027 health providers, out of which 3453 (86%) were clinical healthcare staff. Objective: Determine the per capita cost of the MEBCI interventions towards enhancing new-born care best practices through capacity trainings for frontline clinical and non-clinical staff. Methods: Parameters for determining per capita cost of the new-born care interventions were estimated using expenditure on trainings, supervisions, monitoring and evaluation, advocacy, administrative/services and medical logistics. Data collection started in October 2017 and ended in September 2018. Data sources for the per capita cost estimations were invoices, expense reports and ledger books at the national, regional and district levels of the health system. Results: Total of 4027 healthcare providers benefited from the MEBCI training activities comprising of 3453 clinical staff and 574 non-clinical personnel. Cumulative cost of implementing the MEBCI interventions did not necessarily match the cost per capita in staff capacity building; average cost per capita for all staff (clinical and non-clinical staff) was approximately US 982 compared to a per capita cost of US 799 for training only core clinical staff. Average cost per capita for all regions was approximately US 965 for all staff compared to US 777 per capita cost for only clinical staff. Per capita cost of training was relatively lower in regions with more staff than regions with lower numbers, perhaps due to economies of scale. Conclusion: The MEBCI intervention had a wide coverage in terms of training for frontline healthcare providers albeit the associated cost may be potentially unsustainable for Ghana's health system. Emerging digital training platforms could be leveraged to reduce per capita cost of training. Large-scale on-site batch-training approach could also be replaced with facility-based workshops using training of trainers (TOTs) approach to promote efficiency.
Keywords: 330; Top-down; Bottom-up; New-born care; Marking every baby count initiative; Ghana; Per capita cost; Evaluation; Health policy; Scalability; Sustainability